PARTISIPASI MASYARAKAT DALAM PROSES PERENCANAAN PEMBANGUNAN DI KELURAHAN BOTU KECAMATAN DUMBO RAYA KOTA GORONTALO - Trisusanti Lamangida; Hamid Ibrahim (Universitas Muhammadiyah Gorontalo, 2021)
This study aims to determine community participation in development planning process in the Botu village. This research uses descriptive qualitative research. Data collection techniques use observation, interviews and determination of documentation using three stages of research, namely planning (compiling), implementing and writing reports. While the validity of the data uses triangulation techniques consisting of source and technique. The results showed that community participation in the development process, namely providing ideas, in the form of labor, and participating in providing land to assist the government in the implementation of development. And there are inhibiting factors in the implementation of development, namely the willingness factor and the leadership factor. Keywords: Community Participation, Development Planning